2015
DOI: 10.5897/ajpp2015.4385
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of food colours and additives: A review

Abstract: Majority of consumer goods are required to be presented with good aesthetics in order to improve acceptability in terms of colours and in some instances taste. When related to food, beverages and drug products, additives are usually added to mask un-inviting colours, obscure offensive odours and increase taste. Food additives therefore include colourants, sweeteners, preservatives and anti-caking agents. Admissible daily intake limits are often recommended for these additives. Being food products, the amount c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 113 publications
1
12
0
Order By: Relevance
“…The products of indigo carmine degradation are Isotine-sulfonic and anthranilic acid -intermediary metabolites of tryptophan biosynthesis. Similar results were obtained using Aeromonas hydrophila (Chester, 1901) Stanier, 1943 and mixed cultures (Olusegun & Olajire, 2015).…”
Section: Discussionsupporting
confidence: 75%
“…The products of indigo carmine degradation are Isotine-sulfonic and anthranilic acid -intermediary metabolites of tryptophan biosynthesis. Similar results were obtained using Aeromonas hydrophila (Chester, 1901) Stanier, 1943 and mixed cultures (Olusegun & Olajire, 2015).…”
Section: Discussionsupporting
confidence: 75%
“…However, frequent incidents show that despite strict legislation, there is still a lack of corresponding supervision and control in the supply chain, especially in the source link of aquaculture. As a water-soluble azo pigment, carmine's super-range use in meat products may lead to carcinogenic and mutagenic effects (Olusegun & Olajire, 2015). It was shown that nitrite will oxidize low hemoglobin to high hemoglobin after entering the blood, and generate nitroso compounds, which can cause cancer or acute poisoning (Doyle, Herman & Dykstra, 1985;Mirvish, 1995).…”
Section: Number Of Ema / Ff Recording Cases Per Typementioning
confidence: 99%
“…Some of food colours and additives were declassified as human carcinogens following the comprehensive evaluation of results of at least three tests; cytotoxicity, genotoxicity and mutagenicity in vitro and some in vivo to guarantee safety of these colours. (Thomas and Adegoke, 2015).…”
Section: Synthetic Food Colours Impactsmentioning
confidence: 99%